Elegy - Levis, Larry; Levine, Philip, 1928-2015. (Pittsburgh, Pa. : University of Pittsburgh Press, 1997)
A few days before his death in 1996, Larry Levis mentioned to his friend and former instructor Philip Levine that he had "an all-but-completed manuscript" of poems
The poems were written in the six years following publication of his previous book, The Widening Spell of the Leaves, and continue and extend the jazz improvisations on themes that gave those poems their resonance. There are poems of sudden stops and threats from the wild: an opossum halts traffic and snaps at pedestrians in posh west Los Angeles; a migrant worker falls victim to the bites of two beautiful black widow spiders; horses starve during a Russian famine; a thief, sitting in the rigging of Columbus's ship, contemplates his work in the New World.
The collection culminates in the elegies written to a world in which culture fragments; in which the beasts of burden - the horses, the migrant workers - are worked toward death; a world in which "Love's an immigrant, it shows itself in its work./ It works for almost nothing"; a world in which "you were no longer permitted to know, / Or to decide for yourself, /Whether there was an angel inside you, or whether there wasn't."
Foreword / Philip Levine -- The Two Trees -- In 1967 -- The Oldest Living Thing in L.A. -- Anastasia & Sandman -- Photograph: Migrant Worker, Parlier, California, 1967 -- Shiloh -- The Poem Returning as an Invisible Wren to the World -- The Thief in the Painting -- Boy in Video Arcade -- The Cook Grew Lost in his Village, the Village in the Endless Shuffling of Their Cards -- The Smell of the Sea -- Elegy with a Petty Thief in the Rigging -- Elegy for Whatever Had a Pattern in It -- Elegy with the Sprawl of a Wave Inside It -- Elegy with a Thimbleful of Water in the Cage -- Elegy with a Bridle in Its Hand -- Elegy for Poe with the Music of a Carnival Inside It -- Elegy with an Angel at Its Gate -- Elegy with a Chimneysweep Falling Inside It.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Print version record.
eBooks on EBSCOhost
Keywords: American poetry -- 20th century; Poésie américaine -- 20e siècle.; LITERARY CRITICISM -- Poetry; POETRY -- American -- General; American poetry; 1900-1999; Poetry (Poetic Works By One Author); Poetry